Revelry, rivalry, and longing for the goddesses of Bengal: the fortunes of Hindu festivals - McDermott, Rachel Fell (Columbia University Press, 2011)
Pūjā origins and elite politics -- The goddess in colonial and postcolonial history -- Durgā the daughter : folk and familial traditions -- The artistry of Durgā and Jagaddhātrī -- Durgā on the Titanic : politics and religion in the Pūjā -- The "orientalist Kālī" : a Tantric icon comes alive -- Approaches to Kālī Pūjā in Bengal -- Controversies and the goddess -- Deva in the diaspora -- Appendix : an overview of the press in Bengal up to 1947